Argentina : Income Support Policies toward the Bicentennial - World Bank (Washington, DC, 2013)
Argentina approaches its bicentennial as an independent republic; it has a window of opportunity in social protection policy. Following the most serious economic crisis in its history during 2001-02, the country mobilized an unprecedented effort to provide income support to the population in need. Now, as growth has returned and social indicators have recovered to pre-crisis levels, there is an opening to move from emergency income support programs to a more comprehensive, long-term, and sustainable strategy for social protection. The emergency response was effective, as it helped the country to overcome the worst of the crisis. The centerpiece of the strategy, plan Jefes y Jefas, provided benefits to nearly two million households during a period when poverty affected more than half the population and unemployment reached record levels. The number of beneficiaries slowly declined beginning in 2003, and was at nearly one-third of its maximum value by early 2008. This reduction was achieved by the reentry of beneficiaries into the formal labor market, the loss of eligibility, and the shift of beneficiaries to familias and seguro de capacitacion y empleo (Seguro), the successor programs to Jefes. Now that the crisis has passed, the policy debate has shifted toward the future of social protection over the longer term. The improvement in overall economic conditions since 2003 has resulted in a decline in unemployment, poverty, and inequality, and a recovery of formal employment and real salaries to pre-crisis levels. These positive trends have generated opportunities to consider longer-term and structural issues, including a debate over the future of whether this new type of noncontributory social policies, based on income transfers to households and individuals, should continue.